ANALISIS RASIO KEUANGAN DALAM MENDETEKSI KECURANGAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017 – 2019 - Salsabila Firdausya; Mutiara Tresna Parasetya (Diponegoro Journal of Accounting, 2021)
This study aims to determine the financial ratios that affect fraudulent financial statements. The independent variables used in the test include liquidity ratio by calculating current ratio, leverage ratio by calculating debt to assets ratio and debt to equity ratio, and profitability ratio by calculating return on assets, return on equity, gross profit margin, operating profit margin, and net profit margin. While the dependent variable is fraudulent financial statements. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange in 2017 - 2019. This study uses 60 samples of financial reports, consisting of 30 fraud financial reports and 30 non-fraud financial reports. To test the hypothesis, a logistic regression test was performed. This research shows that the leverage ratio by measuring debt to assets ratio (DAR) has a significant positive effect on fraudulent financial statements. In addition, the results show that gross profit margin (GPM) ratio has a significant negative effect on fraudulent financial statements. Meanwhile, current ratio, debt to equity ratio, return on assets, return on equity, operating profit margin, and net profit margin based on test results are not significant in determining the possibility of financial statement fraud.